Management of Dystocia in Dromedary Camel through Fetotomy - P Patel, Deep; B Solanki, Gajendra; M Kapadiya, Falgun; V Patel, Anshu; R Chaudhary, Gangaram (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Dystocia, or difficult birth, is a significant reproductive concern in animals, often leading to severe complications  for both the dam and the fetus. Although camels are known  for their relatively low incidence of dystocia compared to  other livestock; dystocia in camels, particularly dromedaries,  has been sporadically reported, and are attributed to both  fetal and maternal causes (Gera and Datt, 1981; Purohit et  al., 2000). Dystocia in camelids is uncommon, but the long  neck and fetal limbs make them more prone to flexion  deformities, which are frequent causes of dystocia (Purohit,  2012). Tibary et al. (2008) projected that around 5% of all  camelid deliveries will necessitate some form of assistance,  with nearly 2% requiring specialized obstetrical intervention.  Similarly, Aboul-Fadle et al. (1990) reported a 9% incidence of  dystocia in camels. Dystocia should be suspected in camels  if the first stage of labour extends beyond 6 h, accompanied  by rising pain or discomfort, or if the second stage fails to  progress as expected (Noakes et al., 2019). Fetal causes, such  as limb flexion and lateral deviation of the head and neck  in anterior presentation, accounted for 54.54% and 36.36%  of all fetal-related dystocia cases, respectively (Purohit et  al., 2011). Epidural anaesthesia, typically with 5-10 mL of 2%  lignocaine, is recommended for pain management. If the  cervix is only partially dilated, a Cesarean section should  be considered as an alternative (Thangamani et al., 2018).  Additionally, sufficient space in the birth canal is necessary for  the fetotomy, and proper restraint of the animal is essential  for a safe and effective procedure (Schultz et al., 2008). This  report documents the successful management of dystocia  in a dromedary camel through fetotomy.
Keywords: Dystocia; significant; reproductive; severe